2005
DOI: 10.1063/1.1988984
|View full text |Cite
|
Sign up to set email alerts
|

Direct experimental evidence of hybridization of Pb states with O2p states in ferroelectric perovskite oxides

Abstract: This work presents the O K-and Ti L 3,2-edge x-ray absorption near-edge structure ͑XANES͒ spectra of Pb x Sr 1−x TiO 3 ͑P x STO͒ and Ba x Sr 1−x TiO 3 ͑B x STO͒ compounds with various Pb and Ba concentrations. The result provides direct evidence that the Pb-O bonding strongly affects O 2p-Ti 3d hybridization in the TiO 6 octahedron of P x STO. In contrast, the Ba-O bonding does not substantially affect O 2p-Ti 3d hybridization in B x STO. The Ti L 3-edge XANES spectra show the splitting of the e g band for P x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 17 publications
(18 reference statements)
11
35
0
Order By: Relevance
“…Jan et al attributed a similar behavior observed with the Pb 1Àx Ca x TiO 3 compound to the substitution of Ti by Ca atoms, which decreases the Ti displacement in relation to its centrosymmetric position [27]. On the other hand, this e g orbital splitting was not observed in the XANES spectra of Ba 1Àx Sr x TiO 3 (BST) compounds, and the peak labeled D was adjusted by a simple Gaussian function [51]. In that case, the absence of e g splitting was attributed to an insignificant tetragonal distortion or a lower c/a ratio, which means that the Ti atoms occupy the centrosymmetric positions of the TiO 6 octahedra [51].…”
Section: Resultsmentioning
confidence: 79%
“…Jan et al attributed a similar behavior observed with the Pb 1Àx Ca x TiO 3 compound to the substitution of Ti by Ca atoms, which decreases the Ti displacement in relation to its centrosymmetric position [27]. On the other hand, this e g orbital splitting was not observed in the XANES spectra of Ba 1Àx Sr x TiO 3 (BST) compounds, and the peak labeled D was adjusted by a simple Gaussian function [51]. In that case, the absence of e g splitting was attributed to an insignificant tetragonal distortion or a lower c/a ratio, which means that the Ti atoms occupy the centrosymmetric positions of the TiO 6 octahedra [51].…”
Section: Resultsmentioning
confidence: 79%
“…35 Jan et al obtained the covalent Pb-O bonding strongly affects O 2p-Ti 3d hybridization in the TiO 6 octahedron while the ionic Ba-O bonding does not substantially affect O 2p -Ti 3d hybridization results in Pb-induced tetragonal distortion in the TiO 6 octahedron and ineffectiveness in Ba substitution to Sr-site in SrTiO 3 . 36 The covalence or ionic bonds were strongly related to the difference of electro-negativity between A-and B-site with O in perovskite. To further understanding the mechanism of enhancement in spontaneous and reduction of the band gap due to lithium substitution in A-site BNKT-based, the tolerance factor and difference average electronegativity between A-site with O as function of lithium dopants are analyzed and shown in the Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The separation between L 3 and L 2 edges is due to spin-orbit coupling, which splits the Ti 2p core state into Ti 2p 3/2 (L 3 ) and 2p 1/2 (L 2 ) by about 5.5 eV similar to those of other perovskites. 17 Ti 3d band at both L 3 -and L 2 -edge split into t 2g and e g sub-bands with a $2.5 eV separation by the crystal field, which depends on the polarization. 18 The main difference between the absorption spectra of PZTs and PTO is that the double structure of PTO (indicated by two solid bars) becomes a single feature b 2 of PZTs.…”
mentioning
confidence: 99%